Mahabharata - Slavitt, David R., 1935- (Book collections on Project MUSE., 2015)
Within its 200,000 verse lines in Sanskrit the Mahabharata takes on many roles: epic poem, foundational text of Hinduism, and, more broadly, the engaging story of a dynastic struggle and the passing of an age when man and gods intermingled. David R. Slavitt's sparkling new edition condenses the epic for the general reader. At its core, the Mahabharata is the story of the rivalry between the Pandavas and the Kauravas, two related noble families who are struggling for control of a kingdom in ancient northern India. Slavitt's readable, plot-driven, single-volume account describes an arc from the conception and birth of Bhishma to that hero's death, while also introducing the four goals of life at the center of Hinduism: dharma (righteousness, morality, duty), artha (purpose), kāma (pleasure), and moksa (spiritual liberation). The Mahabharata is engaging, thrilling, funny, charming, and finally awesome, with a range in timbre from the impish naivete of fairy tales to the solemnity of our greatest epics, and this single-volume edition is the best introduction available.